Diagnostic Role of Anti-Nuclear Antibodies in Rheumatic Diseases - Murat BİRTANE, (Archives of Rheumatology, 2012)
Autoimmune diseases result from the assault of the host antibodies against host antigens. The systemic rheumatic diseases rarely have a single pathognomonic diagnostic criterion due to multiple organ and system involvement. Interestingly, each member of this disease group may be associated with different auto antibody types. The diagnosis depends on clinical features, as well as the auto antibodies detected in the sera of the patients. Antinuclear antibodies (ANA) usually target the specific antigens in the nuclear part of the cell, although they can sometimes show affinity against all types of subcellular structures and cell organelles including cell surfaces, cytoplasm, nuclei, or nucleoli. These may provide important data for an upcoming rheumatic disease, be valuable in the diagnosis and prognosis prediction when they are detected in the sera. Simply, ANA can be measured in two ways; one is the generic ANA for overall evaluation and the second is specific antibody detection for specific diseases. Generic ANA measurement can be performed using immunofluorescence techniques and ELISA. If it is positive, specific antibodies can further be investigated by automated methods. The immunofluorescence ANA testing is still gold standard. They show significance when detected in high titers in clinically suspected patients. Furthermore, staining patterns may provide information for the specific disease, indicating the cellular targets of specific antibodies. Generic ANA is highly sensitive for systemic lupus erythematosus (SLE) and scleroderma, while its specificity is lower in these pathologies. ANA may be found positive in healthy people and patients with many other pathological conditions. Therefore, they may be important to rule out the disease. In contrast to generic ANA, specific antibodies are usually specific for related diseases with a low level of sensitivity. Thus, its presence helps diagnosis, however its absence may not be sufficient to exclude the disease. The main antibodies in this category are anti-dsDNA, antiSmith (Sm), and antiribonucleoprotein (RNP) in the diagnosis of SLE; antihiston antibodies for drug-induced SLE; anti-Ro/SSA - anti La/SSB antibodies for Sjögren syndrome; and anticentromer, anti Scl 70 antibodies for scleroderma.